Trends and inequalities in BCG immunisation coverage among one-year-olds in Sierra Leone, 2008-2019 - Augustus Osborne; Florence Gyembuzie Wongnaah; Camilla Bangura; Bright Opoku Ahinkorah (BMC, 2024)
Abstract Background Bacillus Calmette-Guérin (BCG) vaccination is a cornerstone of childhood immunisation programs, protecting against tuberculosis (TB), a major public health concern. Sierra Leone, a West African nation, faces challenges in achieving equitable and high BCG immunisation coverage. This study delves into the trends and inequalities in BCG coverage among one-year-old children in Sierra Leone between 2008 and 2019. Methods Three rounds of data from the Sierra Leone Demographic and Health Surveys (2008, 2013, and 2019) were used to analysed to examine the inequalities in BCG coverage. Simple measures of inequality [Difference (D) and Ratio (R)] and complex measures of inequality [Population Attributable Ratio (PAR) and Fraction (PAF)] were calculated in the World Health Organization's Health Equity Assessment Toolkit (WHO's HEAT) software. The measures were calculated separately for each of the three surveys for age groups of women, level of education, economic status, residential areas, gender, and sub-national provinces, and their estimates were compared. Results The findings revealed that BCG immunisation coverage in Sierra Leone has increased significantly from 2008 (82.0%) to 2019 (96.3%). Age-related inequalities between children of older mothers (20-49) and younger mothers (15-19) increased from a Difference of -4.7 percentage points in 2008 to 4.8 percentage points in 2019. The PAF increased from zero in 2008 to 0.4% in 2019. This means that in the absence of age-related inequalities, the national average of BCG immunisation coverage would have increased by 0.4%. Economic-related inequalities between children of mothers in Quintile 5 (richest) and Quintile 1 (poorest) decreased from a Difference of 9.2 percentage points in 2008 to 1.2 percentage points in 2019. Educational-related inequalities between children of mothers with secondary/higher education and no education decreased from a Difference of 14.1 percentage points in 2008 to 0.4 percentage points in 2019. The PAF decreased from 13.3% in 2008 to 0.2% in 2019, indicating that without educational-related inequalities the setting average of BCG immunisation coverage would have increased by 0.2%. Place of residence-related inequalities between children of mothers living in urban areas and rural areas decreased from a Difference of 9.3 percentage points in 2008 to 0.7 percentage points in 2019. The PAF decreased from 8.5% in 2008 to 0.5% in 2019 indicating that the national average of BCG immunisation coverage would have increased by 0.5% without place of residence-related inequalities. The sex of the child-related inequalities between male and female children decreased from a Difference of 5.4 percentage points in 2008 to 0.7 percentage points in 2019. The PAF decreased from 3.3% in 2008 to 0.4% in 2019 indicating that the national average of BCG immunisation coverage would have increased by 0.4% without sex of the child-related inequalities. Provincial inequalities decreased from a Difference of 18.5 percentage points in 2008 to 2.3 percentage points in 2019. The PAF decreased from 14.3% in 2008 to 1.1% in 2019 indicating that the national average of BCG immunisation coverage would have increased by 1.1% without provincial inequalities. Conclusion The findings indicate a substantial improvement in BCG immunisation coverage in Sierra Leone among one-year-olds, reflecting successful public health initiatives. However, age-related inequalities have worsened, with coverage among children of younger mothers declining relative to those of older mothers, suggesting a need for targeted interventions for this population. In contrast, economic, educational, sex, and place of residence-related inequalities have notably decreased, indicating progress in equitable access to immunisation across different socioeconomic strata. Additionally, provincial inequalities have decreased significantly, yet a difference of 2.3 percentage points remains, highlighting the need for continued efforts to ensure that all provinces, receive adequate healthcare resources and outreach. The absence of economic-related inequality by 2019 is particularly encouraging, as it suggests that economic barriers to immunisation have been effectively addressed. Furthermore, the reduction in educational and provincial inequalities highlights the effectiveness of strategies aimed at improving access and awareness in underserved areas.